Effect of Mg on the Structural, Optical and Thermoluminescence Properties of Li3Al3(BO3)4: Shift in Main Glow Peak - Adil Alshoaibi; Patrick O. Ike; Assumpta C. Nwanya; Chawki Awada; Shumila Islam; Fabian I. Ezema (Molecules, 2023)
The doping of magnesium on lithium aluminium borate phosphor is reported in this study. A solid-state sintering technique was employed as the borate samples were synthesized. This report focuses on the structural, optical, thermoluminescence, and kinetic analyses of the main glow peak. The structural properties of lithium aluminium borates improved due to the magnesium dopants used. Differences in the crystallite size and particle size were 38.85–67.35 nm and 50–60 nm, respectively, and these results were obtained from the analyzed X-ray diffractogram and scanning electron spectroscopy. The energy band gaps obtained from the direct transition of borate phosphor materials were within the range of 3.00–4.40 eV, and the doped samples gave a higher energy band gap. A decrease in the TGA (%) exhibited a weight loss or water loss for the undoped, 0.1% Mg, and 0.3% Mg-doped lithium aluminium borate materials. The glow curve measured at a heat rate of 1 °C·s−1 after irradiation to 50 Gy revealed four peaks related to the magnesium doped lithium aluminium borate. The main glow peak was observed at 86 °C. Activation energy was extracted from the main glow peak by using kinetic analysis which involves the initial rise, deconvolution, and variable heating rate approach, and it was approximately 0.67 ± 0.03 eV. A shift in the main glow peak curve from 86 to 110 °C was recognized for the magnesium-doped lithium aluminium borate when it was irradiated from 1 to 300 Gy.